PENGARUH PENERAPAN STRATEGI PEMBELAJARAN LEARNING CYCLE DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 18 SIJUNJUNG - Nurhalimah, Nurhalimah; mukhni, mukhni; Melisa, Melisa (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was motivated by the lack of mathematical concepts understanding in class VIII SMP 18 Sijunjung. Students were less active in following the learning process of mathematics. This study aims to determine how the activity of learning and students understanding of mathematical concepts using Learning Cycle accompanied Handout. This research was an experimental study. Design of research is random subject. The instrument used in this study was the observation sheet activity and the final test of learning outcomes in the form of essays.Â Based on the analysis of data observation sheet, this was known that the activity of learning activities of students had increased. The average learning outcomes of experimental class at the end of the test was = 86,81 and the average grade control = 75,38. Through t-test, the results of testing the hypothesis were t-test = 3,8 and t-table = 1,6785. Here t-test > t-table. In conclusion, the students understanding of mathematical concepts using Learning Cycle with Handout is better than the understanding of students mathematical concepts using the conventional teaching.